GEOGRAPHIC-VARIATION IN APIS-CERANA-INDICA F - A SPATIAL AUTOCORRELATION ANALYSIS OF MORPHOMETRIC PATTERNS - Diniz, JAF; Malaspina, O.; Pignata, MIB (Int Bee Research Assoc, 1993)
Spatial patterns of morphometric variation in Apis cerana indica were analysed. Factor and spatial autocorrelation analyses were applied to 29 characters, measured in 17 populations in India. Correlograms showed that 15 characters are patterned geographically, and 13 of them are related to overall size. These characters are distributed as a north-south cline, probably reflecting adaptations to environmental conditions. However, the great number of characteristics without geographical pattern suggests that part of the morphometric variability is due to local stochastic divergences.
Keywords: HONEY BEES; APIS-CERANA; MORPHOMETRICS; SPATIAL AUTOCORRELATION; MULTIVARIATE ANALYSIS; FACTOR ANALYSIS; GEOGRAPHIC VARIATION; ZOOGEOGRAPHY; BIOLOGICAL SURFACES; CLINES; INDIA